Interventional oncology treatments for unresectable early stage HCC in patients with a high risk for intraprocedural bleeding: Is a single-step combined therapy safe and feasible?. Issue 114 (May 2019) - Iezzi, Roberto; Pompili, Maurizio; Posa, Alessandro; Carchesio, Francesca; Siciliano, Massimo; Annicchiarico, Brigida Eleonora; Agnes, Salvatore; Giuliante, Felice; Garcovich, Matteo; Cerrito, Lucia; Ponziani, Francesca Romana; Basso, Michele; et al.
Abstract: Purpose: This study was designed to assess the feasibility and safety of a single-step combined therapy using radiofrequency ablation and transarterial chemoembolization (RFA + TACE) in patients with hepatocellular carcinoma (HCC) and uncontrolled coagulopathy. The study also aimed to compare the effectiveness of this approach with TACE alone, performed in a control group. Material and methods: One hundred and forty-three consecutive cirrhotic patients having a single HCC < 8 cm were enrolled in this observational prospective single-center study from January 2010 to June 2017 and were divided, according to coagulation tests, into three groups (A: low risk; B: intermediate risk and C: high risk of bleeding). The feasibility and safety of a single-step combined treatment (RFA followed by TACE) were evaluated in terms of technical success rate, periprocedural complications, and laboratory values variations. Tumor response obtained at 1-month CT follow-up for group C was compared with that of control group, composed by 16 matched patients with severe coagulopathy and single HCC < 8 cm, who underwent only TACE in a previous period, performed by the same operator. Results: Technical success was achieved in all patients, without any major complications. Minor complications rate was significantly higher in group C after RFA; however, the patients were successfully treated with subsequent TACE therapy, without any differences between pre- and post-procedural laboratory values. One-month complete response rates were similar in all the three groups; however, the response rates of group C were significantly higher as compared to that of the control TACE Group (p < .001). Conclusion: The single-step RFA plus TACE therapy allows expansion of the indication for percutaneous thermal ablation, allowing to also include cases previously contraindicated due to the procedural high-risk of complications associated with bleeding, thus improving short-term patient outcome.